Non-Formal Education Policy in Indonesia - Wiharjo, Suyadi Murdi; Wulandari, Dian (Journal of Multi-Disciplines Science, 2024)
This research aims to identify non-formal education policies in Indonesia. This study uses a qualitative method. The research approach uses literature studies and a descriptive approach. Data was obtained from policy documents and reference journals. The research results show that at the macro level, the non-formal education policy is the 1945 Constitution, Law no. 20 of 2003 concerning the National Education System and Regional Regulations. Then, at the meso level, there is Minister of Education and Culture Regulation Number 49 of 2007 concerning Education Management Standards by Non-formal Education Units, Regulation of the Governor of the Special Capital Region of Jakarta Province Number 67 of 2017 concerning the Implementation and Management of Non-formal Education, several Regent Regulations and Mayor Regulations. In the end, the policy at the micro level is the Mayor of Semarang City Regulation Number 18 of 2023 concerning Technical Guidelines for Providing Honorariums to Non-formal and Non-formal Religious Educators, Corpse Care Officers and Prosperity Officers in Places of Worship. The government, regional heads, and legislators need to pay attention to non-formal education policies at the macro, meso, and micro levels so that the contribution of non-formal education is more optimal in creating superior and competitive human resources.